The climate index-length of stay nexus - Soler-García, Ismael Pablo; Gemar-Castillo, Germán; Correia, Marisol B. (Taylor & Francis, 2020)
This study sought to analyze the effect of the climate of tourists’ region of origin on their length of stay in a specific inland destination as climate of origin has been ignored in previous analyses. The present study collected data from 674 valid surveys of visitors in the selected destination and applied a zero-truncated negative binomial regression model and a Poisson-inverse Gaussian regression model. The results for this destination suggest that climate of origin affects tourists’ length of stay. This finding was obtained via the Poisson-inverse Gaussian regression model because of its greater tolerance to long tail distributions. Similarities and differences were found regarding results for other destinations found in the literature. The present findings further include the non-significant effect of reasons for traveling and tourists’ satisfaction and the significant influence of tourists’ mode of transport, income, and age on length of stay. Cheaper lodging categories also have an important impact on visitors who prefer extended stays.
Keywords: Turismo; Cambios climáticos; Climate index; Inland destination; Length of stay; Regional study; Zero-truncated negative binomial model